Mechanical characteristics analysis of the downhole completion string in the open hole section of a small wellbore - Dong, Liangliang; Yang, Weijian; Li, Hongli; Li, Bo; Zhu, Xiaohua (Frontiers in Mechanical Engineering, 2025)
For horizontal wells with small wellbores and large-diameter pipe strings, pipe sticking is prone to occur during oilfield completion operations. Avoiding pipe sticking can effectively save construction costs. In this paper, dynamics and Hertz contact theory are adopted, taking into account the influence of small wellbores and large-diameter pipe strings. Based on the principle of scaling, an experimental bench for the running-in of completion pipe strings is built, and a three-dimensional finite element model for analyzing the axial force and contact force of the completion pipe strings in the open-hole staged fracturing is established. The variation laws of the wellhead axial force, axial force along the well depth and contact force during the running-in process of the completion pipe strings are analyzed. The results show that with the increase in the packer size and friction coefficient in the open-hole section and the decrease in the radius of the open-hole section, the wellhead axial force will decrease, and the contact force will increase accordingly. The neutral point moves upward, the length of the pipe string section under axial pressure increases, and the pipe strings with buckling deformation are all under axial pressure. The pipe string will first buckle near the kick-off point, and then the buckling will extend upward along the straight section from the kick-off point. Moreover, the closer to the kick-off point, the more severe the buckling. The research in this paper provides a theoretical basis for the decision-making of the running-in of completion pipe strings.